Disparities in Access to Preemptive Repeat Kidney Transplant: Still Missing the Mark?. Issue 1 (27th January 2022) - Vinson, Amanda J.; Kiberd, Bryce A.; West, Kenneth; Mannon, Roslyn B.; Foster, Bethany J.; Tennankore, Karthik K.
Key Points: Preemptive kidney transplant (PKT) is associated with improved survival versus transplant after a period of dialysis. There are inequities in access to repeat PKT. Those with lower education or socioeconomic status, those of Black or Hispanic race, and men are less likely to receive repeat PKT. Visual Abstract: Abstract : Background: The need for repeat transplant due to failing kidney allografts is increasing over time. The benefit of preemptive kidney retransplant (PKre-T) is controversial. Marginalized populations are less likely to undergo their first transplant preemptively; however, whether inequities exist for those undergoing PKre-T is unknown. Methods: We performed a cohort study of adult patients undergoing live and deceased kidney transplant in the United States from 2000 to 2018 identified using the Scientific Registry of Transplant Recipients, and we identified patients with first preemptive kidney transplant (PKT) and PKre-T. In the primary analysis, a multivariable logistic regression was used to identify independent predictors of PKre-T. In secondary analyses, multivariable Cox models were used to determine the association of PKre-T with death-censored and all-cause graft loss. Results: In total, 4910 (15.5%) patients underwent PKre-T, and 43, 293 (19.1%) underwent first PKT. Inequities in access to PKre-T persisted (OR, 0.49; 95% CI, 0.44 to 0.55 for unemployed versus full time; OR, 1.61; 95% CI, 1.14 to 2.25 for graduate school versus not completing high school; OR, 0.61; 95% CI, 0.52 to 0.70 for Black versus White race); 7.1% of all transplanted Black patients received PKre-T versus 17.4% of White patients. Women were more likely to undergo PKre-T than men (OR, 1.42; 95% CI, 1.29 to 1.57). PKre-T was associated with superior graft survival relative to retransplant after a period of dialysis (HR, 0.73; 95% CI, 0.67 to 0.80 for all-cause graft failure; HR, 0.72; 95% CI, 0.65 to 0.81 for death-censored graft loss). Conclusions: Despite improved patient and graft survival, inequities in access to PKre-T persist. Patients with lower education, patients with reduced employment status, patients of Black race, and men are less likely to receive PKre-T.